Effect of yttrium solubility on the structural and optical properties of Bi1.5-xYxZn0.92Nb1.5O6.92 pyrochlore ceramics - (:unkn) unknown (ELSEVIER SCI LTD, 2013)
In this article, the yttrium solubility effects on the structural, dielectric and optical properties of the Bi1.5-xYxZn0.92Nb1.5O6.92 (Y-BZN) solid solutions are investigated. The yttrium content (x) was varied in the range of 0.04-0.6. The scanning electron microscopy and energy dispersion analysis have shown that the single phase of the yttrium doped pyrochlore is possible up to yttrium content of 0.06. At x=0.07 YNbO4 minor phase appears and at x=0.08 YNbO4 and ZnO dominates in the Y-BZN. Due to the very rare amount and the random distribution of the minor phases in the pyrochlore, the X-ray diffraction technique was not able to detect these minor phases at low yttrium doping levels. While the nonstoichiometric phase evaluated at x=0.07 displayed no role on the relative density, the dielectric constant, dielectric loss, the temperature coefficient of dielectric constant, the absorbance and the energy band gap are observed to be sharply altered. The energy band gap of the pure BZN widened from 3.30 eV to 3.60 eV when the BZN was doped with Y content of 0.04. It then sharply shrunk to 2.75 eV for Y content of 0.07. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Yttrium doping; Transmittance; Energy gap; Dielectric constant; DIELECTRIC-PROPERTIES; ZINC; FILMS